APPLICATION OF ECONOMETRIC METHODS IN OPERATIONAL PLANNING - Babich В.В (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The applied aspect of the use of statistical models in the operating activities of the company is discussed in the article. The author offers a statistical model that allows you to determine the demand function, based on which you can predict the volume of sales and the forecast to be included in the current operational plans. The author provides a calculation algorithm that allows you to build a model with a certain quality assessment and reliable results using econometric methods. The purpose of the model is the selection of independent factor characteristics that have the strongest effect on changes in sales. A multiple regression model is being constructed. The author puts forward hypotheses and, using tests and certain statistical coefficients, checks them at a certain confidence interval. Given that any entrepreneur is faced with the task of maximizing profits in a certain competitive environment, the task of identifying factors that have a significant impact on demand is extremely important.